Dissolution of Kapok in Ionic Liquid - Mohd Shafiq Luqman b Sulong, Mohd Shafiq Luqman (Universiti Teknologi Petronas, 2011)
The report is to discuss research on ―Dissolution Kapok in Ionic Liquid‖. The project has done some experiments of ionic liquid interaction with kapok in a laboratory and also by studying the ionic liquid journals and articles. Many journals and articles have much new information regarding the dissolution of biomass such as bamboo, rice corn, and many more. It regenerates cellulose back with a new quality. However, none have done dissolving the kapok into ionic liquid which make the author to have some curios on how successful to dissolve kapok in ionic liquid. This report consists of five sections. The first section is on the introduction part of the project which is background study of the project, problem statement and objective. The next section is on the literature review, for there will be a brief theory on the ionic liquids regarding that able to dissolve some biomass materials. The third chapter which is methodology that covers on the experiment procedures in laboratory. The fourth section is result and discussion, where the discovery on dissolving kapok is shown. The final chapter is the conclusion and recommendations that can be apply to improve the project.